Energy characterization of charcoal produced in North Central México - De la Cruz-Montelongo, Carlos; Herrera Gamboa, Jaime; Ortiz Sánchez, Ixchel Abby; Ríos Saucedo, Julio César; Rosales Serna, Rigoberto; Carrillo-Parra, Artemio (Instituto de Ecología, A.C., 2020)
The charcoal produced in Mexico comes from different species and processes, so that its characteristics have a wide variation. The objective was to characterize the charcoal produced in the North Central region of México according to international standards of quality and energy. Three bags of nine commercial provenances of mesquite charcoal (Prosopis sp.), ebony (Ebenopsis sp.) and oak (Quercus sp.), were randomly collected. Readings were obtained for particle size, volatile material, moisture content, fixed carbon, calorific value and the elements Mg, Ca, Cu, Zn and Fe. Data were subjected to analysis of variance under a completely randomized design with four replications per bag and comparison of means were developed with Tukey test. It was found a predominance of 20 mm > X ≤ 50 mm size, only two provenances showed fragments > 100 mm. Mean values were: moisture content 5.1%, volatile material 25.9%, ash 6.3% and fixed carbon 62.7%. The highest calorific value was 27 669 kJ kg-1 and higher values for Ca (177 267 mg kg-1) and Mg (20 263 mg kg-1). Provenances 5, 7 and 8 showed more fixed carbon and volatile material. The variation was related to plant species, provenance as well as the method of production. It is necessary to improve charcoal quality according to particle size, fixed carbon and calorific value; as well as low levels for moisture content, volatile material, and ash content. The constant evaluation of these characteristics will improve the quality of the coal produced in México and facilitate its trading in the international markets.